The study of Gamow-Teller strength in the 51V(p,n)51 Cr reaction at intermediate energies - Tshivhase, Victor Makondelele (Department of Physics, 2016)
The ⁵¹V(p,n)⁵¹Cr reaction was studied at four different proton beam energies namely 90, 120, 160, and 200 MeV. The experiment was performed in the angular range between 0 and 4°, using the beam swinger facility at National Accelerator Centre(NAC) at Faure, near Cape Town. The cross sections of the ground state, Isobaric Analog State, and the giant Gamow-Teller resonance were calculated at 0° for each beam energy. The ratio of the cross section of the giant Gamow-Teller resonance to the cross section of the Isobaric Analog State were studied at beam energies 90, 120, 160 and 200 Me V, and beam angles 0, 2 and 4 °. The Gamow-Teller strength was estimated for energies 120, 160 and 200 MeV. The fractions of Fermi and Gamow-Teller strength in the Isobaric Analog State were also estimated.